A Memory of Concrete: Politics of Representation and Silence in the Agostinho Neto Memorial - Martins, Vasco; Cardina, Miguel; Rocha, Manuela (Kronos: Southern African Histories, 2019)
Focusing on the Memorial António Agostinho Neto (MAAN) in Angola as the case study to analyse materialisations of memory, the article attempts to read the political representations of this monument by analysing its main narratives, questioning its silences and unpacking its impact on public memory. To do so, the article is divided into three parts. The first section engages with the relevant academic literature on southern African memorialisation and provides a brief description of the MAAN. The second and third sections consider Richard Werbner’s notion of elite memorialism to produce a two-dimensional analysis, referencing the absence of MPLA narrative and symbols in the MAAN while noting how it became inaccessible to the ordinary Angolan population, a result of more ample dynamics of state society relations in the country. It concludes that the logics of social hierarchy that have promoted the marginalisation of segments of the population have impacted the MAAN’s ability to contribute to the new ways Angolans are imagining the nation.